Agriculture, technological change and the environment in Latin America: a 2020 perspective - Trigo, Eduardo J. (International Food Policy Research Institute, 1995)
Trigo looks at the elements of a strategy for technological development and institutional change to promote the goals of agricultural intensification, poverty alleviation, and resource conservation. He notes that the need for technological research and development covering a broad mix of products is growing. As population dynamics change, the number of urban poor will outstrip the rural poor, increasing the demand for basic foods. Trigo contends that demand for the crops produced by smallholders will increase, their incomes will rise, and investment in technology and resource conservation will be more attractive to them.